2021
DOI: 10.1111/imj.14874
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to guidelines regarding anticoagulation and risk factors for progression of atrial fibrillation in a nurse‐led clinic

Abstract: Background: Atrial fibrillation (AF) is the commonest cardiac arrhythmia associated with an increased risk of stroke. Evidence suggests that management in a specialty clinic improves clinical outcomes of patients. Aims: To assess level of adherence to evidence-based guidelines regarding anticoagulation and the risk factors for progression of AF in a nurse-led AF clinic. Methods: A retrospective analysis was conducted on clinical records of 136 patients seen at the AF clinic to determine their risk factors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
(90 reference statements)
0
5
0
Order By: Relevance
“…[71] Of note, findings from all of these retrospective studies suggest that studies with lower sample size my underestimate the proportion of patients receiving undertreatment. [18,43,57,69] With the exception of the nurse-led clinic [71], an increasing trend in the proportion of patients receiving undertreatment was observed with increasing sample size. [18,43,57,69]…”
Section: Australasiamentioning
confidence: 97%
“…[71] Of note, findings from all of these retrospective studies suggest that studies with lower sample size my underestimate the proportion of patients receiving undertreatment. [18,43,57,69] With the exception of the nurse-led clinic [71], an increasing trend in the proportion of patients receiving undertreatment was observed with increasing sample size. [18,43,57,69]…”
Section: Australasiamentioning
confidence: 97%
“…However, adherence to guideline recommendations is higher when nurses are involved in the AF clinic and this could be related with better clinical outcomes 39. For example, a recent retrospective study found that the management of AF in a nurse-led clinic was associated with high level of adherence to anticoagulation guidelines 40. Also, an integrated specialised nurse-driven, physician supervised AF clinic demonstrated to reduce all-cause mortality compared with usual care 41.…”
mentioning
confidence: 99%
“…In addition to age, among other risk factors for the development of cardiovascular pathology, the presence of excess weight in patients has been identified as a significant risk factor for the progression of AF [38]. Perhaps for this reason, participants in the IG group, due to their higher adherence to treatment, had a statistically significant lower number of overweight patients compared to participants in the CG group.…”
Section: Discussionmentioning
confidence: 99%